Analisis Kinerja Keuangan Perusahaan Manufaktur Tercatat di BEI Sebelum dan Selama Pandemi Covid-19 - Cindy Anindya Damayanti; Merawati, Endang Etty; Nelyumna (Relevan : Jurnal Riset Akuntansi, 2024)
The objective of this research is to evaluate potential changes in the profitability, liquidity, and solvency ratios during the pre-Covid-19 period compared to the Covid-19 period. Only the firms in the food and beverage sectorthat are currently listed on the IDX will be taken into account for inclusion in this study. The phrase "purposeful sampling" refers to the method used for selecting samples in a deliberate manner. The present research encompasses a cohort of 17 distinct organizations, with an observation period spanning three years and a sample size consisting of 51 persons. Financial ratios are a commonly used approach in the examination of financial performance These ratios will be tested with Return on Equity, Current Ratio, and Debt to Equity Ratio. The present study included doing descriptive statistical analysis, testing for normality, and performing a paired sample t-test using Eviews 12 software. The results of the analysis suggest that (1) there is no significant difference in the profitability ratio between the period before and the period during COVID-19, (2) there is no significant difference in the liquidity ratio between the period before and during COVID-19, (3) and there is no significant difference in the solvency ratio between the period before and during COVID-19.